Simulasi Relokasi Distribusi Jaringan Listrik Tegangan Rendah Menggunakan Simulated Annealing - Abraham Latumahina (ARIKA, 2011)
Application electric poweris either requirement people in now days. The requirement electric power use in hawse until at industrial. 1here is network system a certain make special for user electric, form make electric power talk abaut case network in order to people for can use necessity That problem before by contractor side in building one electric distribution circuit there was one to pass as to interfal circuit that slim to .find obstacle, to consider light for mentioned activity there was one to use with one algorithm logic ( Algorithm Simulated Annealing ) that can to coma and to consider light for to peg out one distribution electric circuit. Simulated annealig can problem that to stand hefor to answer, because to put for to connect with can short -line to find that area, town, line to the amount collect jiff distribution circuit.